MANTRA PENGASIH MANDI ULAR CINTAMANI: KAJIAN STRUKTURAL, FUNGSI, DAN IMPLEMENTASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Syarifah, Siti; Syifanaya, Raissa; Fahira, Dima Azharul; Mulyaningsih, Indrya (Jurnal Tradisi Lisan Nusantara, 2023)
Abstract: This study aims to describe or describe the structure, function, and meaning of the self-compassion mantra, namely the mantra "Mandi Ular Cintamani". The research method used is descriptive method in the form of qualitative, by applying a structural approach. Data collection tools used are listening, reading, and note taking techniques. The validity technique used is triangulation. The data analysis used in this study is the data analysis technique of Miles and Huberman, which contains four components of the data analysis process, including the process of collecting data, reducing data, presenting data, and drawing conclusions. Judging from the results of data analysis, the structure of the spell was found, including: title element, opening element, intention element, suggestion element, purpose element, and closing element. Then, this mantra serves to conquer evil or evil things, fill supernatural powers, a medium of communication with God, amorous charms, and to shackle the human and jinn spirits. Meanwhile, the mantra cintamani snake bath has a figurative or connotative meaning. This research can be applied or implemented in junior high school grade VII odd semester, namely Basic Competency 3.14 and 4.14 about folk poetry.